La mesure statistique et ses limites : l’exemple du système scolaire malgache - Marie-Christine Deleigne (Cahiers de la Recherche sur l'Education et les Savoirs)
While the limitations of censuses and surveys are now frequently stressed, this study rather considers those of administrative data, particularly in education. Beyond quantitative issues (here, the evaluation of respective enrolments in the private and public sectors), the analysis reveals the political and financial stakes bound to education issues. Generated from within the institution itself, school statistics tend to reflect the conditions of their production, and beyond, the state of the educational sector. Particularly, the analysis of the return rate of primary school survey forms in Madagascar in 1999-2000, underlines the symbolic and sociological distance between the actors of the private and public sectors of education, despite a proclaimed political will of close partnership between these two sectors.